Precise determination of the 235U reactor antineutrino cross section per fission - C. Giunti (Physics Letters B, 2017)
We investigate which among the reactor antineutrino fluxes from the decays of the fission products of U235, U238, Pu239, and Pu241 may be responsible for the reactor antineutrino anomaly if the anomaly is due to a miscalculation of the antineutrino fluxes. We find that it is very likely that at least the calculation of the U235 flux must be revised. From the fit of the data we obtain the precise determination σ235=(6.33±0.08)×10−43cm2/fission of the U235 cross section per fission, which is more precise than the calculated value and differs from it by 2.2σ. The cross sections per fission of the other fluxes have large uncertainties and in practice their values are undetermined by the fit.